G20 Economic Growth Analysis Using VECM - Dominique, Nancy Nikentary; Buntaran, Carmen Ibanez Indrawati; Nurhanifah, Ameilia; Ferdinand, Ferry Vincenttius (Jurnal Ilmu Ekonomi Terapan, 2023)
This study analyzes the effect of Gross Fixed Capital Formation (GFCF), Imports, Exports, and Government Expenditure of selected G20 member countries on Gross Domestic Product (GDP) using historical data from 1981 to 2021. The detailed analysis aims to explore the relationship between short-term and long-term causality that begins with examining and testing the degree of integration, Unit Root Test, Johansen cointegration test, and causality test. The Vector Error Correction Model (VECM) test results with a 95% confidence interval show that Gross Fixed Capital Formation causes Australia's and South Africa's long-term GDPs to have reached a balance point. In addition, Government Spending also causes the European Union's Gross Domestic Product to achieve a balance point. Imports affect the GDP of the United States, China, and South Africa towards a balance point, and exports affect the GDP of Australia, China, and South Africa. The test results using VECM also conclude that GDP, GFCF, exports, and imports affect GDP growth in the short term. However, on the contrary, on the Australian continent, only GDP, GFCF, and imports which in the previous year had an impact on Australia's GDP in the short term”concluded that differences in government policies in each country in regulating the economy could affect the causal relationship between the independent variable and GDP in the short and long term.